Antibacterial activities of mechanochemically synthesized perovskite strontium titanate ferrite metal oxide - Zhang, Li (2016)
This work explored strontium titanate ferrite (SrTi1−xFexO3−δ or STFx in short) metal oxide as an effective antibacterial agent and investigated its bactericidal mechanism. The perovskite STFx nanoparticles (x = 0, 0.2, 0.4, 0.6, 0.8 and 1) were successfully synthesized with high energy ball milling approach. The feasibility of utilizing this material for antibacterial application was studied on Escherichia coli (E. coli) in the presence of dispersed STF0.8 nanoparticles in water. Excellent bactericidal effect has been observed by killing all the E. coli (∼105 CFU/mL) within 15 min in both light and dark conditions, excluding photocatalysis as the major contributing mean of bactericidal effect. Mechanism study via surface charge characterization, fluorescence microscope observation, inductively coupled plasma measurement and SEM examination has revealed that the positive surface charge, high pH environment, Sr2+ dissociation and nano-size of STF0.8 metal oxide could have collectively contributed to its excellent bactericidal effect. These results have increased the potential to apply STFx in water purification for microorganism destruction.